Learning History in Strengthening the Characteristics of Pasir Putih Pekanbaru Advens High School Students for the 2022-2023 Academic Year - Jonson Tamba; Ulung Napitu; Franki Siallagan (Pelopor Publikasi Akademika, 2023)
Education is one of the systematic efforts to produce quality future generations. Qualified and professional educators or teachers are an absolute requirement to provide quality education, but the author draws the conclusion that is necessary and most important is the good character of educators or teachers who must be imitated and emulated in order to produce a quality generation as well. Given the importance of these problems, the professionalism and motivation of educators or teachers need to be examined and paid attention to by educators or teachers. It is not an easy job, even a very heavy job if you have not prepared yourself in advance because there are many challenges from students and from society in general because you socialize on a daily basis. -day. Because as an example or as a model, because it is in the hands of the Educator or the Teacher the success of students and the progress of a country, is in the hands of the Teacher.